Peranan Manajer dalam Meningkatkan Kinerja Keuangan PT Bank Syariah Indonesia Tbk - Ade Pratama; Intan Permata; Oktaviana Oktaviana (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This article aims to analyze the role and financial performance of Bank Syariah Indonesia in recent years, focusing on metrics such as Return On Asset (ROA), Return On Equity (ROE), Net Interest Margin (NIM), and Operating Expenses to Operating Income Ratio (BOPO). As an Islamic banking institution, Bank Syariah Indonesia plays a crucial role in mobilizing and channeling funds in accordance with Islamic principles. In the face of the challenges posed by the COVID-19 pandemic, this article highlights the positive growth of Islamic banking assets, indicating a better performance compared to conventional banks. Financial performance analysis, utilizing indicators such as ROA, ROE, NIM, and BOPO, provides insights into the efficiency of asset and capital utilization by Bank Syariah Indonesia. Additionally, the research evaluates the bank's efforts in managing operational expenses to support sustainable operations. The findings of this research offer a comprehensive understanding of the positive contributions of Bank Syariah Indonesia to the Indonesian economy and underscore potential growth in the future. The implementation of Islamic principles in banking operations serves as a foundation that can be adopted by other banking institutions to achieve economic sustainability in alignment with Islamic financial values.